Persepsi Wisatawan Terhadap Kawasan Suci Pura Masceti Di Desa Medahan Kecamatan Blahbatuh Kabupaten Gianyar - Darma, Gede Surya Arta; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i02.p05, 2019)
The Sacred area of ??Masceti Temple is located in Medahan Village, Blahbatuh District. The Number of tourists began increasing is an indication of the tourism potential that can be developed. This is the background of choosing the topic "Tourist Perception of Masceti Temple Sacred Area in Medahan Village" to be studied. This research used qualitative and quantitative study methods those are qualitative descriptive analysis, validity test analysis, reliability test and frequency analysis to know the perception of tourists to the destination. Data sources from primary data and secondary data. Data completion technique using observation method, interview, literature study, documentation, and questionnaire. The technique of determining tourist samples used in this study is a quota sampling technique. The finding of Tourism Potentials are panoramic nature, socio-cultural, artificial or economical and the perception of tourists to destination consist into four aspects those are tourist perception of tourism attraction, tourist perception of access to location, tourists perception of tourism facility and tourist perception of tourism service. From this research can be concluded that The Sacred Area of Masceti Temple already has tourism potentials which is needed for a way for the development that must follow the rules of The Sacred Area of Masceti Temple. So, it can be realized without reducing the sanctity of Masceti Temple as Kahyangan Jagat Temple in Gianyar regency, Bali. Keywords: Tourism Potential, The Sacred Area of Masceti Temple, Medahan Village